China: an East Asian alternative to neoliberalism? - Horesh, Niv; Lim, Kean Fan (Taylor and Francis, 2016)
The political-economic evolution of post-Mao China has been portrayed as a historically inevitable embrace of neoliberalism; as an exemplification of the East Asian developmental state and as an extension of Soviet New Economic Policy-style state capitalism. This paper evaluates these portrayals through a broad historical and geographical framework. It examines the position of China as a new state after 1949. It then places the shifting logics of socioeconomic regulation in China in relation to (1) the global neoliberal hegemony since the 1980s and (2) the concomitant shifts in the economic policies of Japan, South Korea and Taiwan. In so doing, the paper demonstrates how the Communist Party of China creatively adapted and re-purposed regulatory logics from the Washington Consensus and East Asian policies to consolidate its own version of Leninist state-led development.